Reflections on bioethics: consolidation of the principle of autonomy and legal aspects Reflexões em bioética: consolidação do princípio da autonomia e aspectos legais - Marco Segre (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1999)
The author highlights the importance of emotions in all ethical reflections. He describes the most common positions of ethicists employing duties and rights as the basis for ethical thought. The author, goes to Freudian theory as viewed by the utilitarians, stating that the 'quest for pleasure' is not necessarily egocentric, especially for adults. For example, the feeling of solidarity emerges 'from the inside out', making irrelevant all the emphasis laid on obedience to duty (from the outside in). The article questions the essence of Kantian theory, based exclusively on 'reason' with disregard for feelings, by establishing what he considers a 'positivist' view of rational thought. It emphasizes the principle of autonomy, which it seen as basically opposing the principles of beneficence and fairness. It is proposed that the latter should be seen as what he calls heteronomy (a concept different from that of the rational ethicists). In theory, autonomy is not assigned to anyone on the basis of an external assessment. Any intervention in individual autonomy must be made (by the intervenor) when it becomes imperative in the defense of social or cultural values. The article distinguishes between ethics and morals) and states that the sole acceptable ethical principle is that ethics (theoretically) has no principle. O autor destaca a importância das emoções em todas as reflexões éticas. Descreve as posições mais comuns dos eticistas, que empregam deveres e direitos como base para o pensamento ético. O autor refere-se à teoria freudiana, sob o enfoque dado pelos utilitaristas, ao afirmar que a "busca do prazer" não é necessariamente egocêntrica, especialmente para os adultos. Por exemplo, o sentimento de solidariedade emerge de "dentro para fora", tornando irrelevante toda ênfase colocada na obediência ao dever. O artigo questiona a essência da teoria Kantiana baseada exclusivamente na razão, desconsiderando os sentimentos , ao estabelecer o que ele encara como uma visão positivista do pensamento racional. Enfatiza o princípio de autonomia, que é visto como basicamente se opondo aos princípios da beneficência e da justiça. Na teoria, a autonomia não é atribuída a ninguém, tendo como base uma avaliação externa. Qualquer intervenção na autonomia individual precisa ser feita (pelo interventor) quando se torna imperativa a defesa de valores sociais ou culturais. O artigo distingue ética de moral e estabelece que o único princípio ético aceitável é o de que a ética (teoricamente) não possui princípios.